2014
DOI: 10.1155/2014/929536
|View full text |Cite
|
Sign up to set email alerts
|

Change in Growth Differentiation Factor 15, but Not C-Reactive Protein, Independently Predicts Major Cardiac Events in Patients with Non-ST Elevation Acute Coronary Syndrome

Abstract: Among the numerous emerging biomarkers, high-sensitivity C-reactive protein (hsCRP) and growth-differentiation factor-15 (GDF-15) have received widespread interest, with their potential role as predictors of cardiovascular risk. The concentrations of inflammatory biomarkers, however, are influenced, among others, by physiological variations, which are the natural, within-individual variation occurring over time. The aims of our study are: (a) to describe the changes in hsCRP and GDF-15 levels over a period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…[15][16][17][18] GDF15 is easily detectable in the blood; however, concentrations vary with age and gender. 15,[19][20][21] For instance, we have shown that circulating levels of GDF15 can serve as strong independent predictor for cardiovascular events in women but not in men. 22 Although GDF15 has a sex-dependent prognostic value in heart failure patients, 23 the prognostic value of GDF15 is not standardly analysed for men and women separately to increase accuracy.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[15][16][17][18] GDF15 is easily detectable in the blood; however, concentrations vary with age and gender. 15,[19][20][21] For instance, we have shown that circulating levels of GDF15 can serve as strong independent predictor for cardiovascular events in women but not in men. 22 Although GDF15 has a sex-dependent prognostic value in heart failure patients, 23 the prognostic value of GDF15 is not standardly analysed for men and women separately to increase accuracy.…”
Section: Introductionmentioning
confidence: 97%
“…Elevated protein expression of circulating growth differentiation factor 15 (GDF15) is correlated to many pathological conditions, mainly being different types of cancer and also metabolic diseases such as obesity and diabetes 15–18 . GDF15 is easily detectable in the blood; however, concentrations vary with age and gender 15,19–21 . For instance, we have shown that circulating levels of GDF15 can serve as strong independent predictor for cardiovascular events in women but not in men 22 .…”
Section: Introductionmentioning
confidence: 98%
“…GDF15 is a member of the transforming growth factor-beta (TGF-b) superfamily [25]. The expression of GDF15 is elevated in many types of malignancies, cardiovascular diseases, inflammatory diseases and type 2 diabetes [26][27][28][29]. Although the exact role and mechanism are as-yet-unknown, the putative role of GDF15 is as an anti-inflammatory cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…It is pointed that GDF-15 level is associated with the risk of death and myocardial infarction independent of clinical variables and other biomarkers [ 16 ]. Dominguez-Rodriguez et al [ 17 ] measured the level of GDF-15 and high-sensitivity C-reactive protein (hsCRP) in patients with acute coronary syndrome at admission and again 36 months after admission. They found that the change of hsCRP levels, measured after 36 months, does not estimate major cardiovascular adverse events (MACE) in patients with acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%